HOX and PBX gene dysregulation as a therapeutic target in glioblastoma multiforme - Einthavy Arunachalam; William Rogers; Guy R. Simpson; Carla Möller-Levet; Gemma Bolton; Mohammed Ismael; Christopher Smith; Karl Keegen; Izhar Bagwan; Tim Brend; Susan C. Short; Bangxing Hong; et al. (BMC Cancer, 2022)
Abstract Background Glioblastoma multiforme (GBM) is the most common high-grade malignant brain tumour in adults and arises from the glial cells in the brain. The prognosis of treated GBM remains very poor with 5-year survival rates of 5%, a figure which has not improved over the last few decades. Currently, there is a modest 14-month overall median survival in patients undergoing maximum safe resection plus adjuvant chemoradiotherapy. HOX gene dysregulation is now a widely recognised feature of many malignancies. Methods In this study we have focused on HOX gene dysregulation in GBM as a potential therapeutic target in a disease with high unmet need. Results We show significant dysregulation of these developmentally crucial genes and specifically that HOX genes A9, A10, C4 and D9 are strong candidates for biomarkers and treatment targets for GBM and GBM cancer stem cells. We evaluated a next generation therapeutic peptide, HTL-001, capable of targeting HOX gene over-expression in GBM by disrupting the interaction between HOX proteins and their co-factor, PBX. HTL-001 induced both caspase-dependent and –independent apoptosis in GBM cell lines. Conclusion In vivo biodistribution studies confirmed that the peptide was able to cross the blood brain barrier. Systemic delivery of HTL-001 resulted in improved control of subcutaneous murine and human xenograft tumours and improved survival in a murine orthotopic model.